A disability perspective from the United States on the case of Ms B. Issue 4 (1st August 2002) - Coleman, D; Drake, S
Abstract : This article will examine the case of Ms B, a woman with tetraplegia for a year, who, prior to rehabilitation or return to community life, sought a ruling that doctors may turn off her ventilator. The authors are people with disabilities. Their analysis focuses on the manner in which the High Court (a) framed the case in terms of mental capacity, (b) addressed the issue of suicide and ambivalence, and (c) resolved informed consent and treatment alternative issues. While the disability community in the US does not oppose the general right to refuse treatment, there is significant concern about lack of informed consent and denial of desired treatment alternatives, and the cavalier manner in which these factors have been dismissed.